Evaluation of sanitary and veterinary inspection results of slaughtered sheep in Poland in 2017-2019 - Górski, Krzysztof; Niedziółka, Roman; Horoszewicz, Elżbieta (2021)
The aim of this study was to follow and evaluate the sanitary and veterinary inspection results of slaughtered sheep in Poland in the period 2017-2019. More than 175,000 sheep were slaughtered in Poland during this period. Post-mortem veterinary inspection revealed symptoms and/or lesions in 19,799 animals, which constituted 11.30% of all examined sheep. Of these, 134 animals (0.08%) were considered unfit for consumption. The most numerous cases were with foci of pus, contamination and congestion (5.07%) and fasciolosis (4.72%). The highest number of foci of pus, contamination and congestion in sheep carcasses were found in the Małopolskie and Podlaskie voivodeships. Most of the cases deemed unfit for consumption were found in the Podkarpackie (30), Świętokrzyskie (29) and Podlaskie (23) voivodeships, accounting for over 61% of all disqualified sheep carcasses in 2017-2019 in Poland.
Cilj ove studije bio je pratiti i procijeniti rezultate sanitarne i veterinarske inspekcije zaklanih ovaca u Poljskoj u razdoblju 2017. - 2019. godine. Više od 175 000 ovaca je zaklano u Poljskoj u tom razdoblju. Obdukcijska veterinarska inspekcija otkrila je simptome i/ili lezije u 19 799 životinja, što predstavlja 11,30 % svih pregledanih ovaca. 134 zaklane životinje smatrane su neprikladnima za konzumaciju (0,08 %). Najbrojniji su bili slučajevi s gnojnim žarištima, kontaminacijom i kongestijom (5,07 %) i fasciolozom (4,72 %). Najveći broj gnojnih žarišta, kontaminacije i kongestije u lešina ovaca pronađen je u Małopolskie i Podlaskie vojvodstvima. Najviše slučajeva koji su smatrani neprikladnima za konzumaciju pronađeno je u Podkarpackie (30), Świętokrzyskie (29) i Podlaskie (23) vojvodstvima, što je predstavljalo više od 61 % svih lešina ovaca proglašenih neprikladnima za konzumaciju u razdoblju 2017.-2019. godine u Poljskoj.
Bibliografija: 22 jed.
Abstract ; Sažetak.
Keywords: Ovce -- Sanitarna inspekcija -- Veterinarska inspekcija -- Lezije